Understanding the shoot apical meristem regulation: a study of the phytohormones, auxin and cytokinin, in rice - Azizi, Parisa; Yusop, Mohd Rafii; Mahmood, Maziah; Abdullah, Siti Nor Akmar; Musa, Mohamed Hanafi; Abdul Latif, Muhammad; Abdul Rashid, Azmi; Sahebi, Mahbod (Elsevier, 2015)
Auxin and cytokinin regulate different critical processes involved in plant growth and environmental feedbacks. These plant hormones act either synergistically or antagonistically to control the organisation, formation and maintenance of meristem. Meristem cells can be divided to generate new tissues and organs at the locations of plant postembryonic development. The aboveground plant organs are created by the shoot apical meristem (SAM). It has been proposed that the phytohormone, cytokinin, plays a positive role in the shoot meristem function, promotes cell expansion and promotes an increasing size of the meristem in Arabidopsis, whereas it has the reverse effects in the root apical meristem (RAM). Over the last few decades, it has been believed that the apically derived auxin suppresses the shoot branching by inactivating the axillary buds. However, it has recently become clear that the mechanism of action of auxinis indirect and multifaceted. In higher plants, the regulatory mechanisms of the SAM formation and organ separation are mostly unknown. This study reviews the effects and functions of cytokinin and auxin at the shoot apical meristem. This study also highlights the merger of the transcription factor activity with the actions of cytokinin/auxin and their complex interactions with the shoot meristem in rice.